2013
DOI: 10.1093/rheumatology/ket334
|View full text |Cite
|
Sign up to set email alerts
|

Synovial joint fluid cytokine levels in hip disease

Abstract: IL-8 levels in RDC were higher than in the other hip diseases. The IL-8 level may reflect the aggressiveness of joint destruction in RDC, and IL-6 and TNF-α levels may also reflect ongoing destruction in OA and ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
(37 reference statements)
2
32
1
1
Order By: Relevance
“…The discrepancy between the results of the previous studies has been explained by loss of TNF-α activity during storage, presence of specific inhibitors in the SF, transient peaks in TNF-α activity during the disease, and different methods of sample preparation [21, 57, 58]. However, not detecting any TNF-α in our osteoarthritic dogs might also be explained by the chronicity of the disease, as the level of TNF-α has previously been reported to be higher in acute severe joint disease compared to joint disease in general [59], but conflicting findings have also been recently published [22, 60]. …”
Section: Discussionmentioning
confidence: 83%
“…The discrepancy between the results of the previous studies has been explained by loss of TNF-α activity during storage, presence of specific inhibitors in the SF, transient peaks in TNF-α activity during the disease, and different methods of sample preparation [21, 57, 58]. However, not detecting any TNF-α in our osteoarthritic dogs might also be explained by the chronicity of the disease, as the level of TNF-α has previously been reported to be higher in acute severe joint disease compared to joint disease in general [59], but conflicting findings have also been recently published [22, 60]. …”
Section: Discussionmentioning
confidence: 83%
“…Control [1,5,12,18,19,49]; atrophic versus hypertrophic in two studies [13,14]; and radiographic OA classification in five studies [6,23,42,47,48]. Two studies [15,20] analyzed minimum joint space width as a continuous variable relative to biomarker levels.…”
Section: Literature Searchmentioning
confidence: 99%
“…It has been shown that circulating levels of IL-6 are drastically increased during infections or in the contest of other inflammatory conditions, such as autoimmune rheumatic diseases 35,36. Patients with RA show elevated concentration of IL-6 levels both in the serum (ranging from 5 pg/mL to 200 pg/mL, with 1–16 pg/mL being the physiologic range in healthy people) and in the synovial fluid (about 100–1,000 fold higher than controls) 3739. Serum levels of IL-6 in RA patients correlate with disease severity and radiological joint progression 40,41.…”
Section: Introductionmentioning
confidence: 99%